THE INFLUENCE OF THE FAMILY PSYCHOLOGICAL ENVIRONMENT ON PERSONAL DEVELOPMENT (Universal International Scientific Journal, 2026)
This article analyzes the influence of the family psychological environment on the development of the individual from a theoretical and practical perspective. Based on scientific sources, the role of the emotional climate, upbringing style and communication process in the development of the individual is substantiated. The results of the study show that a healthy and stable psychological environment directly affects the social adaptation of the individual, the level of self-awareness and emotional stability.
Keywords: family psychology; psychological environment; personality development